The effectiveness of an immersive virtual reality and telemedicine-based cognitive intervention on prospective memory in Parkinson’s disease patients with mild cognitive impairment and healthy aged individuals: design and preliminary baseline results of a placebo-controlled study - De Simone, Maria Stefania; Costa, Alberto; Tieri, Gaetano; Taglieri, Sara; Cona, Giorgia; Fiorenzato, Eleonora; Carlesimo, Giovanni Augusto; Caltagirone, Carlo; Zabberoni, Silvia (Frontiers in Psychology, 2023)
Introduction: Prospective memory (PM) impairments have been extensively documented in individuals with Parkinson's disease associated with mild cognitive impairment (PD-MCI) and in those with healthy aging. Considering how PM failure decreases individuals' quality of life and functional independence in the activities of daily living, training to enhance this ability could be a prior target of intervention. Objective: Here, we aimed to present the study protocol and preliminary results of a novel immersive virtual reality (IVR) and telemedicine-based (TM) cognitive intervention focused on executive abilities (i.e., planning, shifting and updating) to improve PM functioning in PD-MCI patients and healthy elderly individuals. Methods: Outcome measures, collected before, immediately after and 2 months after the intervention, included: 1) pre-post training changes in objective cognitive functioning, evaluated with tests assessing executive functions and PM; 2) prepost training changes in subjective perception of memory functioning, psychiatric symptoms, autonomy in daily living and quality of life, evaluated using the appropriate scales; 3) usability, feasibility and users' compliance with the proposed IVR and telemedicine program. The efficacy of this intervention compared to an active control condition is currently being evaluated in a randomized, double-blind controlled trial, which will be conducted on 30 eligible PD-MCI patients and 30 older adults. Results: Preliminary results concerning between-group comparisons of demographic and neuropsychological screening data show a good balance among the intervention groups considered in this study. The results also suggest good levels of usability, feasibility and acceptability, thus supporting the notion that our intervention can be used to promote cognitive functioning, even in people with cognitive decline. Conclusion: Considering the relatively low costs and easy accessibility to this program, it could prove valuable in primary prevention initiatives and early cognitive rehabilitation for dementia risk reduction.